Reporting vybrané firmy - Dočekalová, Hana (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Tato diplomová práce zachycuje problematiku reportingu v současných podmínkách podnikání v konkrétním podniku. V první části práce jsou uvedeny teoretické poznatky týkající se reportingu. Druhá část se zabývá analýzou současného stavu reportingu ve vybraném podniku. V poslední části diplomové práce budou na základě analýz navržena doporučení podporující další možný rozvoj reportingu ve vybrané firmě.

The diploma thesis deals with issues concerning reporting in the current business environment in a particular company. In the first chapter you can find theoretical knowledge regarding reporting. The second part focuses on an analysis of the current situation in reporting in a selected company. In the last part of the diploma thesis recommendations supporting further potential development of reporting in the selected company on the base of the analysis will be proposed.
Reporting of the Selected Firm
Keywords: Reporting; controlling; manažerské účetnictví; Reporting; Controlling; Management Accounting